DFT Study of Efinaconazole, an Antifungal Drug and Its Molecular Docking against a Holoenzyme (pdb id: 3IDB) (Journal of Scientific Research, 2021)
Efinaconazole (ECZ) is an antifungal drug. Various non-covalent interactions between ECZ and a holoenzyme (protein id: 3idb) has been investigated through computational study. The structure of ECZ was optimized using density functional theory (DFT) applying B3LYP/6-311G+(d,p) method. HOMO, LUMO, chemical hardness and softness, several thermochemical parameters, electrostatic potential surface, vibrational spectrum, total energy, and maximum internal force and maximum internal displacement with respect to optimization step number have been determined. The optimized ECZ ligand was subjected to molecular docking against the protein 3idb in Autodock Vina program. The different non-covalent interactions in the ligand-protein complex were visualized in BIOVIA Discovery Studio Visualizer. Various surface plots such as hydrogen bonds, ionizability, SAS, hydrophobicity, aromatic and charge surfaces were excerpted. ECZ molecule forms three strong hydrogen bonds with amino acid residues of the holoenzyme. In addition to this, it is significantly capable to form several other bonds which strengthen the ligand-protein interaction. The result showed that the ECZ molecule posed considerable binding affinity against the macromolecule.